Development of the Flipbook e-module with a Scientific Approach Problem Based Learning in Improving Students’ Abstract Skills - Anisah, Aan; Sri Asnawati; Dian Permana Putri (JTP - Jurnal Teknologi Pendidikan, 2023)
The urgency of this research is to help accelerate the implementation of new learning paradigms by meeting the need for learning innovation by using technology to improve students’ abstract skills. The aim of this research is to design and analyze the validity, practicality and effectiveness of the Accounting flipbook e-module as well as improving students’ abstract skills through a scientific approach combined with problem-based learning methods (Problem Based Learning). The research method used is the R&D method using the 4D development model, namely Define, Design, Development and Dissemination. This research was only carried out until the development stage, the dissemination stage was not carried out due to time constraints. Research data collection techniques are in the form of questionnaires such as validation sheets, questionnaires, concept understanding ability tests and documentation. The data analysis technique used is the percentage descriptive technique, namely changing quantitative data into percentage form, then interpreting it using qualitative sentences. The research results obtained include the results of validation of the design of teaching materials in the form of an Accounting flipbook e-module which is in the "Very Eligible" criteria. The results of the student response questionnaire showed the criterion "Very Strong" and the N-gain results between the experimental class and the control class showed differences in students’ abstract skills. Where the experimental class got a result of 0.54 which was greater than the control class of 0.37. So it can be concluded that the flipbook e-module design in this research is valid, practical and effective.